Structuring Clinical Workflows for Diabetes Care - Schweitzer, M.; Lasierra, N.; Oberbichler, S.; Toma, I.; Fensel, A.; Hoerbst, A. (Applied Clinical Informatics, 2014)
Background: Electronic health records (EHRs) play an important role in the treatment of chronic diseases such as diabetes mellitus. Although the interoperability and selected functionality of EHRs are already addressed by a number of standards and best practices, such as IHE or HL7, the majority of these systems are still monolithic from a user-functionality perspective. The purpose of the OntoHealth project is to foster a functionally flexible, standards-based use of EHRs to support clinical routine task execution by means of workflow patterns and to shift the present EHR usage to a more comprehensive integration concerning complete clinical workflows.Objectives: The goal of this paper is, first, to introduce the basic architecture of the proposed OntoHealth project and, second, to present selected functional needs and a functional categorization regarding workflow-based interactions with EHRs in the domain of diabetes.Methods: A systematic literature review regarding attributes of workflows in the domain of diabetes was conducted. Eligible references were gathered and analyzed using a qualitative content analysis. Subsequently, a functional workflow categorization was derived from diabetes-specific raw data together with existing general workflow patterns.Results: This paper presents the design of the architecture as well as a categorization model which makes it possible to describe the components or building blocks within clinical workflows. The results of our study lead us to identify basic building blocks, named as actions, decisions, and data elements, which allow the composition of clinical workflows within five identified contexts.Conclusions: The categorization model allows for a description of the components or building blocks of clinical workflows from a functional view.Citation: Schweitzer M, Lasierra N, Oberbichler S, Toma I, Fensel A, Hoerbst A. Structuring clinical workflows for diabetes care: An overview of the OntoHealth approach. Appl Clin Inf 2014; 5: 512–526 http://dx.doi.org/10.4338/ACI-2014-04-RA-0039
Keywords: Electronic health records; medical records; diabetes mellitus; workflow; semantics